Strategi Pembinaan Akhlak Santri Yang Berusia Di Bawah 10 Tahun - Shofwatal Qolbiyyah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2021)
This study aims to find out how the moral development strategy of students under the age of 10 years at TPQ Al-Ma'ruf Sukorame Lamongan and what factors are supporting and inhibiting the implementation of the coaching and how to overcome them. This research is a qualitative research, taking the background of TPQ Al-Ma'ruf Sukorame Lamongan. Data collection is done by observation, interviews, and documentation. Data analysis in this study uses data reduction, data display and conclusion. From the results of this study, it shows that the strategy of moral development of students under the age of 10 years at TPQ Al-Ma'ruf Sukorame Lamongan uses several methods, namely the habituation method, the noble exemplary method (uswah hasanah), the demonstration method, the advice method, the exemplary method. story.